Chuyển đổi số trong các doanh nghiệp nhỏ và vừa tại Việt Nam: Phương pháp nghiên cứu tích hợp mô hình TOE và TAM - Nguyễn Thị , Loan; Đỗ Thị Hồng , Vân; Lê Thị , Nương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study proposes integrating TOE and TAM models to provide a comprehensive perspective on the direct and moderating effects of various factors on the digital transformation process in small and medium-sized enterprises in Vietnam. Data were collected from 335 enterprises. The PLS-SEM method was employed to test hypotheses. The findings indicated that the key factors in the TOE framework have a direct positive impact on the digital transformation, except for regulatory policy. Perceived usefulness and perceived ease of use in the TAM model play a positive partial moderating role in the relationship between technological platform, information security, and the digital transformation. The results provide managerial implications for enhancing firm innovation capacity, optimizing technology adoption, and improving business performance